How Can Learning Lesser Used Languages Wide Out Our Frontiers? (a contribution to the theory and practice of intercultural communication) - Mutavdzic, Predrag; Stojicic, Vojkan (International Journal of Language, Translation and Intercultural Communication, 2015)
In last decades a special attention has been paid to intercultural communication and its development in societies all around the world. A number of cultural anthropologists describe it as an informal face-to-face verbal/oral interaction between individuals representing different cultures (Asante-Gudykunst, 1989:14; Prosser, 1978:102). In addition, in a number of scientific papers one can read that this subtype of human communication can have its key success only if it is based on the premise of the equal use of different languages and of their respect. Article 2:3 of the Lisbon Treaty itself states that the European Union “shall respect its rich cultural and linguistic diversity, and shall ensure that Europe's cultural heritage is safeguarded and enhanced” (OJEU, 2007:11). The truth is that intercultural communication, as one part of communication in general, is a necessity for successfully bridging the gap between different cultures and languages. In the European Union intercultural exchange and communication among the European nations are the imperative for a united international (economical, political, social etc.) cooperation in which foreign language learning has a special social and political priority. However, inside the borders of the European Union there is a large group of official languages which are lesser used and, consequently, not widely learnt (e.g. Polish, Hungarian, Lithuanian, Catalonian, Welsh etc.). In the Balkans all official national languages together with other spoken minority ones belong to this group according to Ferguson`s sociolinguistic classification. Viewing intercultural communication as a profound social phenomenon, Singer (1998:41) undoubtedly pointed out that when different groups encounter one another, a common problem is that people think differently. According to the theories of cognitive anthropology, this always occurs because of the existence of either slightly or completely different cultural models in societies. To be achieved a deeper and comprehensive intercultural communication and its effectiveness, which both involve reduction in a large measure of uncertainty and anxiety related to otherness and building a new perceptive scheme about others, learning lesser used languages, such as Greek in Serbia and Serbian in Greece, is considered a categorical request for any further constructive development of relations and cooperation between different nations within and outside the European Union.